(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Changing lifestyle is responsible for increase in number of people suffering from Hypertension, Stress, Diabetes mellitus, Obesity, Heart ailments and other Non Communicable diseases. Among these life-style disorders hypertension is an important public health challenge worldwide. The disease Hypertension has no such clear cut reference in Ayurvedic texts. Eminent Ayurvedic scholar Vaidhya Brihaspati Dev Triguna Padam Vibhushan correlated high blood pressure with Vyana BalaVridhi. He postulated that increased Vyana Bala is responsible for increased Arterial pressure. Present study was conducted to explore evidence based therapeutic potential of Shankhpushpyadi Yoga in the management of Vyan Bal Vriddhi w.s.r. to Hypertension. The patients fulfilling the inclusion criteria and voluntarily wiling for trial were registered from O.P.D. & I.P.D. Dept. of Kayachikitsa R.G.G.P.G.AYU Hospital, Paprola. The Clinical trial was approved by I.E.C. The trial formulation contains Hydroalcoholic extract of Shankhpushpi 150 mg, Bhumyamlaki 250 mg, Punarnava 200 mg, Jatamanshi and Sarpagandha 100 mg each. Clinical trial was of 45 days and total 30 patients were registered for the same.After45days analysis revealed that out of 30 patients, 4 patients showed excellent improvement,15 showed marked, 7 showed mild improvement and no improvement was noted in 2 patients. The mean systolic blood pressure before treatment was 148.71 mm of Hg which dropped to 140.14 mm of Hg at the end of 45 days therapy, with 5.28% reduction. The mean diastolic blood pressure before treatment was 95 mm of Hg which dropped to 87.142 mm of Hg at completion of trial with 8.27% reduction which was statistically significant. Shankhpushpyadi yoga proved to be an effective and safe remedy for patients of Hypertension.